ASSESSING THE EMOTIONAL INTELLIGENCE LEVEL AND ANALYZING ITS IMPACT ON THE WELL-BEING OF IT/ITES PROFESSIONALS - WITH SPECIAL REFERENCE TO SOUTH INDIA - Ranganathan, Deepa (Journal of Contemporary Research in Management (JCRM), 2013)
The dissertation aims to assess the EmotionalIntelligence levels of the IT/ITES employees of South India and bring out itsimpact on the well-being state of the employees. This will enable the creativeuse of the EI concept in the sector and thereby increase its contributiontowards our nation’s economy